Dust reduction agent, cement composition, and spraying method of concrete
A polymer-based dust reduction agent with specific glass transition and stress properties, integrated into a cement composition, addresses the inefficacy of existing dust reduction methods, providing enhanced dust suppression in concrete blowing.
Patent Information
- Application Number
- JP2023116578
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-18
- Publication Date
- 2025-01-30
AI Technical Summary
Existing concrete blowing methods generate excessive dust, which is not adequately addressed by conventional dust reduction agents focusing on polyethylene oxide viscosity and granularity, necessitating a more effective solution.
A dust reduction agent comprising a polymer with a glass transition temperature of -30 °C or less and a first normal stress difference of 100 to 2500 Pa in a 5% aqueous solution at 100 s^-1, combined with a cement composition, is used to reduce dust during concrete blowing.
The proposed solution effectively reduces dust by identifying the glass transition temperature and first normal stress of the polymer, achieving superior dust suppression in concrete blowing processes.
Smart Images

Figure 2025014227000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a dust-reducing agent, a cement composition containing the dust-reducing agent, and a method for spraying concrete using the cement composition. [Background technology]
[0002] Conventionally, concrete spraying has been used to reinforce exposed natural ground during tunnel excavation and to stabilize the excavated surface. For example, a wet spraying method is commonly used in which materials are measured and mixed in a measuring plant installed at the excavation site to prepare concrete, and the concrete is then pneumatically transported by a piston pump or the like while an accelerator is supplied from the other branch pipe of the junction pipe to mix the concrete and the accelerator, and the concrete is then sprayed from a nozzle.
[0003] In addition, a dry spraying method has been proposed in which water is added to the dry-mix concrete during pneumatic transport, a powdered quick-setting admixture is supplied to a branch pipe of a junction pipe, the concrete and the quick-setting admixture are mixed, and then the concrete is sprayed from a nozzle.
[0004] These spraying methods may generate a large amount of dust when spraying the pneumatically transported concrete. The Ministry of Health, Labor and Welfare's "Guidelines for dust control measures in tunnel construction work, etc." (No. 07200 No. 2, July 20, 2020) states that the dust concentration target level is 2 mg / m 3 The government has set the limit as follows: It is necessary to reduce the amount of dust at concrete spraying construction sites. In addition, since experimental measurement of the amount of dust requires a large-scale spraying test, there is a demand for a dust-reducing agent that can predict the dust-reducing effect in advance.
[0005] As a dust countermeasure, for example, a wet spraying method is disclosed in which a hydraulic composition is produced by mixing solid polyethylene oxide under mixing conditions according to the viscosity of cement, water, aggregate, and an aqueous solution of polyethylene oxide, a solid quick-setting agent is mixed with the hydraulic composition to produce a hydraulic composition for spraying, and the hydraulic composition for spraying is sprayed onto an object, the water / cement ratio of the hydraulic composition for spraying being 50% by mass or more and 70% by mass or less (see Patent Document 1).In addition, a dust-reducing agent for wet sprayed concrete is disclosed, which contains a water-soluble ether and polyethylene oxide, and is characterized in that the polyethylene oxide contains 70% by mass or more of particles with a particle size of 150 μm or less (Patent Document 2). [Prior art documents] [Patent documents]
[0006] [Patent Document 1] Patent No. 7136972 [Patent Document 2] JP 2004-189529 A Summary of the Invention [Problem to be solved by the invention]
[0007] The conventional dust control methods described above focus on the viscosity of polyethylene oxide in an aqueous solution and the particle size. However, as a result of investigations conducted by the present inventors, not only was it found that the viscosity of polyethylene oxide in an aqueous solution and the particle size alone were not sufficient to achieve a sufficient dust-reducing effect, but it was also found that dust-reducing agents containing polymers other than polyethylene oxide can also effectively reduce dust.
[0008] In view of the above, an object of the present invention is to provide a dust-reducing agent having an excellent dust-reducing effect by specifying the glass transition temperature and first normal stress difference of the polymer contained therein. [Means for solving the problem]
[0009] As a result of intensive research conducted in light of the above-mentioned problems, the present inventors have found that a dust-reducing agent containing a polymer having a predetermined glass transition temperature, in which the first normal stress difference of an aqueous solution of the polymer is within a predetermined range, can solve the above-mentioned problems, and have completed the present invention.
[0010] [1] A dust-reducing agent containing a polymer having a glass transition temperature of -30°C or less, wherein a 5% by mass aqueous solution of the polymer is dissolved at a temperature of 20°C and a shear rate of 100 s -1 A dust-reducing agent having a first normal stress difference (N1) of 1 to 2500 Pa. [2] The dust-reducing agent according to [1] above, containing 10% by mass or more of the polymer. [3] A dust-reducing agent according to [1] or [2] above, further comprising a water-reducing agent. [4] The dust-reducing agent according to any one of the above [1] to [3], further comprising talc. [5] A cement composition comprising cement and the dust-reducing agent according to any one of [1] to [4] above. [6] The cement composition according to [5] above, wherein the content of the dust-reducing agent is 0.01 to 10 parts by mass per 100 parts by mass of the cement. [7] The ratio (N1 / η) of the first normal stress difference (N1) of the polymer in the dust-reducing agent to the viscosity (η) of a cement composition to which water is added at a water / cement ratio of 0.1% at a temperature of 20°C is 0.1 to 0.5 s -1 The cement composition according to the above [5] or [6], [8] A method for spraying concrete, comprising using the cement composition according to any one of [5] to [7] above. Effect of the Invention
[0011] According to the present invention, a dust-reducing agent having an excellent dust-reducing effect can be provided by specifying the glass transition temperature and first normal stress difference of the contained polymer. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] Hereinafter, an embodiment of the present invention (the present embodiment) will be described in detail, but the present invention is not limited to the embodiment. In addition, "%" in this specification is based on mass unless otherwise specified.
[0013] [Dust reducing agent] The dust-reducing agent according to the present embodiment is a dust-reducing agent containing a polymer having a glass transition temperature of -30°C or lower, and is a 5 mass% aqueous solution of the polymer at a temperature of 20°C and a shear rate of 100 s -1 The first normal stress difference at the
[0014] The polymer used in the present invention has a glass transition temperature of -30°C or lower, preferably -45°C or lower, and more preferably -50°C or lower. If the glass transition temperature of the polymer is higher than -30°C, dust may not be reduced. In the present invention, the glass transition temperature of the polymer can be measured, for example, by a dynamic viscoelasticity measuring device DMA (DMA1 manufactured by Mettler Toledo). The measurement conditions are as follows: sample thickness 150 μm, width 4 mm, chuck distance 20 mm, temperature rise from -150°C at a temperature rise rate of 3°C / min, dynamic viscoelasticity is measured in a linear region within a measurement strain of 0.15%, and a frequency of 1 Hz, and the temperature at the maximum value of tan δ can be evaluated as the glass transition temperature.
[0015] The polymer used in the present invention is a 5% by weight aqueous solution at a temperature of 20°C and a shear rate of 100 s -1 The first normal stress difference in is 1 to 2500 Pa, preferably 100 to 2000 Pa, and more preferably 500 to 1500 Pa. If the first normal stress difference is less than 1 Pa, dust may not be reduced, and if it exceeds 2500 Pa, pumpability of concrete may be reduced. Note that in the present invention, the first normal stress difference is measured, for example, using a commercially available rotational rheometer (manufactured by Anton Paar: MCR302) with 50 mm parallel plates, a gap of 0.5 mm, a measurement temperature of 20° C., and a shear rate of 100 s -1However, if measurement is difficult due to the accuracy of the measuring device, twice the storage modulus, known as the Cox-Merz rule of thumb, can be used as an alternative physical property. The storage modulus can be measured by dynamic viscoelasticity measurement using a double-gap measuring tool in the same device as above, at a measurement temperature of 20°C and a measurement angular frequency of 100 rad / s.
[0016] The above polymer may be any of natural polymers, semi-synthetic polymers, and synthetic polymers, and may have a linear or branched molecular structure. For example, polyethylene oxide, polyacrylamide, polyvinyl alcohol, etc. may be used. Here, the first normal stress difference can be adjusted by controlling the molecular weight of the polymer. Since the first normal stress difference is expressed from the elastic properties in the system, for example, when the molecular weight of the polymer is increased, the number of entanglement points increases, and the first normal stress difference is easily increased. However, the viscosity also increases. In the case of a branched polymer, it varies depending on the molecular weight of the branched chain, but a branched chain that is long enough to be entangled easily increases the first normal stress, and a branched chain that is not long enough to be entangled decreases the viscosity, so in the case of a branched polymer, not only the molecular weight of the branched chain but also the molecular weight distribution affects it, and the first normal stress difference and viscosity can be adjusted by controlling these. The average particle size of the polymer measured using a laser diffraction scattering method is preferably 300 to 800 μm, more preferably 400 to 700 μm.
[0017] The dust-reducing agent according to the present embodiment preferably contains the above polymer in an amount of 10% by mass or more, more preferably 25% by mass or more, and even more preferably 30% by mass or more. Also, the amount is preferably 60% by mass or less, more preferably 45% by mass or less, and even more preferably 40% by mass or less. When the content of the polymer in the dust-reducing agent is within the above range, the dust-reducing effect can be improved.
[0018] The dust-reducing agent according to the present embodiment preferably further contains a water-reducing agent. By containing a water-reducing agent, the dust-reducing agent is likely to have a more excellent dust-reducing effect. As the water-reducing agent, a high-performance water-reducing agent, a high-performance AE water-reducing agent, an AE water-reducing agent, a fluidizing agent, etc. can be used, and any of polycarboxylate-based, naphthalenesulfonate-based, melaminesulfonate-based, and ligninsulfonate-based can be used, and one or more of these may be used.
[0019] The content of the water reducing agent in the dust-reducing agent is preferably 0.1 to 10 mass%, more preferably 1 to 10 mass%, and even more preferably 1 to 5 mass%. When the content of the water reducing agent is within the above range, the dust-reducing effect is more excellent.
[0020] The dust-reducing agent according to the present embodiment preferably further contains talc. Talc is highly slippery and has low hygroscopicity, so when the dust-reducing agent contains talc, the talc covers the surface of the polymer and prevents it from becoming ball-shaped when it comes into contact with moisture, making it easier to dissolve uniformly when added to concrete, and making it easier to improve the dust-reducing effect.
[0021] The content of talc is preferably 10 to 300 parts by mass, more preferably 50 to 200 parts by mass, and even more preferably 75 to 150 parts by mass, relative to 100 parts by mass of the polymer in the dust-reducing agent. When the content of talc is within the above range, the dust-reducing effect is easily improved.
[0022] The dust-reducing agent according to this embodiment may further contain known additives such as an antifoaming agent, if necessary.
[0023] [Cement composition] The cement composition according to the present embodiment contains cement and the dust-reducing agent of the present invention. By containing the dust-reducing agent in the cement composition, it is possible to exhibit an excellent dust-reducing effect when used in sprayed concrete or the like.
[0024] The cement according to the present invention is not particularly limited, and examples thereof include various Portland cements such as normal, early strength, super early strength, low heat and moderate heat, various mixed cements obtained by mixing these Portland cements with blast furnace slag, fly ash, silica fume, etc., environmentally friendly cements (eco-cements) manufactured using municipal waste incineration ash and sewage sludge incineration ash as raw materials, commercially available fine particle cements, white cements, etc., and various cements can be used in a fine powder form. In addition, cements adjusted by increasing or decreasing the amount of components (e.g., gypsum, etc.) normally used in cements can also be used. Furthermore, a combination of two or more of these can also be used.
[0025] In the cement composition according to the present embodiment, the content of the dust-reducing agent is preferably 0.01 to 10 parts by mass, more preferably 0.05 to 8 parts by mass, and even more preferably 0.1 to 5 parts by mass, relative to 100 parts by mass of cement. When the content of the dust-reducing agent in the cement composition is within the above range, an excellent dust-reducing effect can be exhibited when used in sprayed concrete or the like.
[0026] The cement composition according to the present embodiment preferably contains aggregate. The aggregate is not particularly limited, and is preferably one having a low water absorption rate and high aggregate strength. As the type of aggregate, either fine aggregate or coarse aggregate can be used. As the fine aggregate, river sand, mountain sand, sea sand, lime sand, silica sand, etc. can be used. As the coarse aggregate, river gravel, mountain gravel, lime gravel, etc. can be used. Crushed sand and crushed stone can also be used.
[0027] The fine aggregate ratio in the cement composition is preferably 50 to 80 volume %, more preferably 55 to 70 volume %. When the fine aggregate ratio is within the above range, when used in sprayed concrete, etc., pumpability is good and excellent dust reduction effect can be achieved. The fine aggregate ratio can be calculated as the volume of all fine aggregates relative to the volume of all aggregates in the cement composition (s / a).
[0028] The cement composition according to the present embodiment has a ratio (N1 / η) of the first normal stress difference (N1) of the polymer in the dust-reducing agent of the present invention to the viscosity (η) of the cement composition to which water is added at a water / cement ratio of 0.1%, measured at a temperature of 20° C. -1 It is preferable that the range is 0.2 to 0.45 s. -1 More preferably, the range is 0.25 to 0.4 s -1 It is more preferable that the ratio is 1 / η. When N1 / η is within the above range, excellent dust reduction effect can be achieved when sprayed onto concrete. Here, the above N1 / η tends to decrease when the content of the dust reducing agent in the cement composition is increased, and tends to increase when a water reducing agent is added to the cement composition. In the present invention, the above N1 / η can be calculated by mixing the cement composition and water in a mixer or the like to a predetermined water / cement ratio, and measuring the viscosity at a temperature of 20°C using a rheometer with a 50 mm parallel plate and a gap of 1 mm.
[0029] The cement composition according to the present embodiment can be produced by mixing the cement and the dust-reducing agent with a mixer or the like. When the cement composition contains aggregate, it is preferable to add the dust-reducing agent to the aggregate in advance. As an addition method, for example, the dust-reducing agent is added when the aggregate is measured, and then the dust-reducing agent is mixed with the cement with a mixer or the like to produce the cement composition.
[0030] [How to spray concrete] The concrete spraying method according to the present embodiment uses the cement composition of the present invention. By using the cement composition of the present invention in the concrete spraying method, the amount of dust can be effectively reduced when spraying concrete.
[0031] The concrete spraying method according to the present embodiment can be applied to both wet spraying and dry spraying methods. When applied to the wet spraying method, the cement composition and water are mixed in advance to prepare concrete, which is then sprayed. When applied to the dry spraying method, the water-free cement composition is mixed with water just before spraying, and the concrete is sprayed.
[0032] In the concrete spraying method according to the present embodiment, the water / cement ratio is preferably 40 to 60%, more preferably 45 to 55%, and even more preferably 50 to 55%. When the water / cement ratio is within the above range, the amount of dust can be effectively reduced when spraying the concrete.
[0033] In the concrete spraying method according to this embodiment, either a liquid quick-setting admixture or a powder quick-setting admixture can be used as the quick-setting admixture, and it is also possible to use both in combination.
[0034] The concrete spraying method according to this embodiment can be carried out by pneumatically transporting the cement composition through the transport pipe with compressed air, and pneumatically transporting the quick-setting agent through the transport pipe from the other branch pipe of the junction pipe with compressed air, and after the cement composition and the quick-setting agent are mixed together, spraying the concrete from a nozzle. For example, "MKW-25SMT" (manufactured by Shintech Co., Ltd.) can be used to pump the cement composition, and for example, "Natmcrete" (manufactured by Chiyoda Seisakusho Co., Ltd.) can be used to pump the quick-setting agent. EXAMPLES
[0035] The present invention will be described in more detail below using examples and comparative examples. However, the present invention is not limited to the following examples as long as it does not deviate from the gist of the present invention.
[0036] <Measurement of glass transition temperature> In the present invention, the glass transition temperature of the polymer was measured by a dynamic viscoelasticity measuring device DMA (DMA1 manufactured by Mettler Toledo). The measurement conditions were a sample thickness of 150 μm, width of 4 mm, and chuck distance of 20 mm, and the temperature was raised from -150°C at a heating rate of 3°C / min. The dynamic viscoelasticity was measured at a frequency of 1 Hz in a linear region within a measurement strain of 0.15%, and the temperature at the maximum value of tan δ was evaluated as the glass transition temperature.
[0037] <Measurement of the first normal stress difference> In the present invention, the first normal stress difference was measured using a rotational rheometer (Anton Paar: MCR302) with 50 mm parallel plates, a gap of 0.5 mm, a measurement temperature of 20°C, and a shear rate of 100 s -1 However, when measurement was difficult due to the accuracy of the measuring device, twice the storage modulus, known as the Cox-Merz rule of thumb, was used as an alternative property. The storage modulus was measured by dynamic viscoelasticity measurement using the same device as above, with a double-gap measuring tool from the same manufacturer, at a measurement temperature of 20°C and a measurement angular frequency of 100 rad / s.
[0038] <Polymer> Polymer A: Polyethylene oxide, density: 1.2g / cm 3 , average particle size: 500μm. Polymer B: Polyethylene oxide, density: 1.2 g / cm 3 , average particle size: 650μm. Polymer C: Polyethylene oxide, density: 1.3 g / cm 3 , average particle size: 610 μm. Polymer D: Polyethylene oxide, density: 1.2 g / cm 3 , average particle size: 600μm. Polymer E: Polyethylene oxide, density: 1.3g / cm 3 , average particle size: 580μm. Polymer F: Polyethylene oxide, density: 1.3 g / cm 3 , average particle size: 610 μm. Polymer G: Polyvinyl alcohol, density: 1.3 g / cm 3 , average particle diameter: 550 μm. Polymer H: Polyvinyl alcohol, density: 1.2 g / cm 3 , average particle diameter: 600 μm.
[0039] <Preparation of dust reducer> Using the above polymers and the materials shown below, a dust reducer was prepared so as to have the contents described in Table 1, respectively.
[0040] <Materials used> Water reducing agent: Polyethylene glycol-based water reducing agent. Talc: Density: 2.81 g / cm 3 , average particle diameter 10 μm.
[0041] <Preparation of cement composition> Using the materials shown below and the prepared dust reducer, 360 kg of cement, 1049 kg of fine aggregate, 716 kg of coarse aggregate, and 0.36 kg of dust reducer were mixed to prepare a cement composition.
[0042] <Materials used> Cement: Ordinary Portland cement, specific gravity 3.15 g / cm 3 . Fine aggregate: River sand produced in Himekawa, Niigata Prefecture, specific gravity 2.61 g / cm 3 . Coarse aggregate: Crushed stone produced in Himekawa, Niigata Prefecture, specific gravity 2.67 g / cm 3 .
[0043] <Measurement of N1 / η> Water was added to the prepared cement composition so as to be 0.1 part by mass with respect to 100 parts by mass of the cement in the cement composition, and the mixture was mixed for 1 minute with a mixer (manufactured by Shinky Co., Ltd.: ARE-310). Using a rotational rheometer (manufactured by Anton Paar Co., Ltd.: MCR302), with a 50 mm parallel plate used and a gap of 1 mm, the viscosity at a temperature of 20°C was measured, and the ratio (N1 / η) of the first normal stress difference of the polymer to the obtained viscosity was calculated. The results are shown in Table 1.
[0044] <Spraying concrete> Water was added to the prepared cement composition in an amount of 0.1 parts by mass per 100 parts by mass of cement in the cement composition, and mixed. Concrete was then sprayed by a wet spraying method using a commercially available quick-setting admixture ("Denka calcium aluminate quick-setting admixture").
[0045] <Dust concentration measurement> Ten minutes after spraying, measurements were taken at a fixed position 5 m from the spraying site using a digital dust meter (LD-5R, manufactured by Shibata Scientific Co., Ltd.). The results are shown in Table 1.
[0046] [Table 1] [Industrial Applicability]
[0047] The dust-reducing agent of the present invention can be suitably used, for example, in tunnels such as roads, railways, and waterways, and for spraying concrete on exposed natural ground surfaces such as slopes.
Claims
1. A dust-reducing agent comprising a polymer having a glass transition temperature of −30° C. or lower, A 5% by mass aqueous solution of the polymer was subjected to a shear rate of 100 s at a temperature of 20°C. -1 First normal stress difference (N 1 ) is 1 to 2500 Pa.
2. The dust-reducing agent according to claim 1 , comprising 10% by mass or more of the polymer.
3. The dust-reducing agent according to claim 1 or 2, further comprising a water-reducing agent.
4. 3. The dust reducing agent of claim 1 or 2, further comprising talc.
5. A cement composition comprising cement and the dust-reducing agent according to claim 1 or 2.
6. The cement composition according to claim 5, wherein the content of the dust reducing agent is 0.01 to 10 parts by mass per 100 parts by mass of the cement.
7. The first normal stress difference (N 1 )and, The ratio of the viscosity (η) of the cement composition to which water was added at a water / cement ratio of 0.1% and the viscosity (η) measured at a temperature of 20° C. (N 1 / η) is 0.1 to 0.5 s -1 6. The cement composition of claim 5, wherein
8. A method for spraying concrete, comprising using the cement composition according to claim 5.
Citation Information
Patent Citations
Dust reduction agent for wet spray concrete, and wet spray concrete
JP2004189529A
Wet spraying method
JP7136972B2